COMPARISON BETWEEN SYSTEMS ENVIRONMENTAL ASSESSMENT IN SHEDS OF LAYING HENS IN THE REGION OF DOURADOS - MS - Santos, R. C.; Battilani, M.; Garcia, R. G.; Geisenhoff, L.; Jordan, R. A. (Revista Brasileira de Engenharia de Biossistemas, 2014)
Seeing that environmental factors such as temperature and relative humidity influence on animal production, they should be observed with the greatest possible accuracy, thereby, avoid making decisions based on distorted data. Thus, the objective of this work was to collect climate data near a shed to produce laying hens and compares them with those measured by an official climate agency for possible deviations owing to the geographical distance. The experiment was conducted in the Dourados - MS, with climate data collected in UFGD and Embrapa Agropecuária Oeste in April 2014. Eight random days where the temperature was checked, wind speed and relative humidity were chosen. Through the mean values of temperature and humidity index (THI) values obtained for the shed and official data it was concluded that the ITU curve acquired for official climate agency is an ideal location for the reality of Dourados-MS curve, but their data do not represent the local situation as in loco in the hottest time of day.